2023
DOI: 10.1021/acs.jpclett.2c03657
|View full text |Cite
|
Sign up to set email alerts
|

Enhance Hydrogen Isotopes Separation by Alkali Earth Metal Dopant in Metal–Organic Framework

Abstract: Kinetic quantum sieving (KQS) based on pore size and chemical affinity quantum sieving (CAQS) based on adsorption site are two routes of porous materials to separate hydrogen isotope mixtures. Alkali earth metals (Be, Mg, and Ca) were doped into UiO-67 to explore whether these metal sites can promote H 2 /D 2 separation. Based on the zero-point energy and adsorption enthalpy calculated by density functional theory calculations, the Be dopant shows better H 2 /D 2 separation performance than other alkali earth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…[58] Kim et al reported a highly effective hydrogen isotope separation system based on MOF-74-IM-Ni 2+ by implementing the strategy of combining KQS and CAQS for the first time. [13] To date, hydrogen isotope separation based on CAQS has been studied in different kinds of MFU-4l, [60] Hofmann-type, [63] and (Be, Mg, and Ca)-doped [64] MOFs, which have shown excellent selectivities of D 2 -over-H 2 above liquid nitrogen temperatures. Recently, metal-ion-exchanged zeolites such as Cu(I)-ZSM-5, [56] Ag(I)-ZSM-5, [25] and Ag(I)-exchange zeolite Y [57] have been investigated for their excellent potential for hydrogen ion separation based on CAQS.…”
Section: Chemical Affinity Quantum Sieving (Caqs)mentioning
confidence: 99%
See 3 more Smart Citations
“…[58] Kim et al reported a highly effective hydrogen isotope separation system based on MOF-74-IM-Ni 2+ by implementing the strategy of combining KQS and CAQS for the first time. [13] To date, hydrogen isotope separation based on CAQS has been studied in different kinds of MFU-4l, [60] Hofmann-type, [63] and (Be, Mg, and Ca)-doped [64] MOFs, which have shown excellent selectivities of D 2 -over-H 2 above liquid nitrogen temperatures. Recently, metal-ion-exchanged zeolites such as Cu(I)-ZSM-5, [56] Ag(I)-ZSM-5, [25] and Ag(I)-exchange zeolite Y [57] have been investigated for their excellent potential for hydrogen ion separation based on CAQS.…”
Section: Chemical Affinity Quantum Sieving (Caqs)mentioning
confidence: 99%
“…[14,16] Extremely high energy consumption, high cost, complex operational procedures, and low selectivity/separation factors are the main limitations of existing isotope separation technologies such as cryogenic distillation, [50] Girdler sulfide processing, [51] and thermal cycling absorption processes (TCAPs). [52] To develop a promising alternative method for separating hydrogen isotopes, several experimental and molecular simulation (MS) studies have revealed that various functional porous materials such zeolites, [15,25,33,[53][54][55][56][57] metal organic frameworks (MOFs), [8,9,13,14,[58][59][60][61][62][63][64] covalent organic frameworks (COFs), [65] nanoporous carbons, [66,67] metal organic cages, [68] and porous organic cages [69] exhibiting high porosity, ultrasmall pores, and diverse functionalities can selectively capture and separate hydrogen isotopes by relying on "quantum sieving" (QS). In porous materials such as zeolites and MOFs, hydrogen isotopes separation can be realized with high selectivity through "kinetic quantum sieving" (KQS) and "chemical affinity quantum sieving" (CAQS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deuterated solvents serve as the source of deuterium in the synthesis of next generation OLEDs. The separation of H 2 and D 2 on metal organic frameworks (MOFs) has been recently gaining both theoretical and experimental attention. Although a plethora of applications of perdeuterated materials emerge in the area of medicine and the design of new materials, in the latter case, the isotopic substitution of heavy atoms may need to develop even faster, as exemplified by the isotopic effect of heat dissipation in the nanomaterial realm. In this area, nontraditional methods of isotopic enrichment seem to be on the way to rapid development.…”
mentioning
confidence: 99%